PENDIDIKAN DAN PARTISIPASI POLITIK DALAM MASYARAKAT KOMUNITARIAN DI ACEH SINGKIL - Darwin, Rizkika Lhena; Lidya, Lidya (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2019)
Community Education Levels in 3 Villages namely: Gosong East Telaga Village, Ketapang Indah Village, Kampung Baru Village in North Singkil District, Aceh Singkil District are very low, but the level of participation in the direct election of the Village Head in North Singkil District is high. The high voter turnout reaches 60%, while the low voters value 40%. The high level of electoral participation generated by the participation of low-educated people involved with contributions and elections during the Direct Election of the Village Head. This paper wants to explain about the communitarian culture that is very strong in society so that it encourages politics for a sense of family, and encourages people to vote not because of rationality. Thus there was no education participation in the number of community participation in the village head election in 3 Singkil Utara Sub-Districts, Aceh Singkil District.